The Design Model of Halal Product Assurance Implementation - Dewi, Nur Diana; Hamzah, Muhammad Zilal; Sofilda, Eleonora (UNISSULA, 2023)
The majority of Indonesia's population is Muslim in the amount 87.21% of a total of 237 million people. However, this is not directly proportional to the lack of halal product certification in Indonesia. The study aims to determine the implementation of halal product assurance certification in Indonesia by analyzing the Indonesia and Malaysia certification without neglecting the readiness of LPPOM MUI and BPJPH in facing changes to the halal certification regulations of JPH Law. The research method was the interview and FGD techniques. The data was processed by NVivo 12. The implication of this research shows that the JPH Law can organize effectively with the hard work of BPJPH to synergize the stakeholders. The implementation model of halal product assurance adjusted to the strategy and work plan for JPH by emphasizing the increasing stakeholder involvement, G2G Cooperation, and SME Development.